Caracterización funcional del gen PhaZ en plantas - Ortiz, Ana Veronica; Frare, Romina Alejandra; Gomez, Maria Cristina; Jozefkowicz, Cintia; Ayub, Nicolás Daniel; Blumwald, Eduardo; Soto, Gabriela Cynthia (Ministerio de Desarrollo Agrario - Instituto Tecnológico de Chascomús, 2025)
Poster